ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGGAJIAN KARYAWAN (STUDI KASUS : PT. KOSAMBI LAKSANA MANDIRI) - Oktaviani K; Joni Devitra (LPPM Universitas Dinamika Bangsa, 2017)
Payroll system for companies mostly have used computer technology or computer-based informationsystems, but there are still some companies that do not implement them as well as on PT. KosambiLaksana Mandiri. In this company in the payroll system is still using manual calculation and use theauxiliary program MS. Excel. The goal in this study Analyze and study the problems of employee payrollinformation system at PT. Kosambi Laksana Mandiri and produce a prototype system of employee payrollinformation on PT. Kosambi Laksana Mandiri. System design in this study using a UML (UnifiedModelling Language) that use case diagrams, activity diagrams and class diagrams. Meanwhile, in themanufacture of a prototype system using MySQL tools for designing the database and AdobeDreamweaver CS5 to design a prototype system. In this study generates payroll information systemprototype PT. Like a Kosambi Mandiri to manage computerized payroll data, perform calculations salaryevery month automatically and presents reports required salary every month or every year.